Redes sociales en la web. Comunicación y comportamiento social - La Rosa Pinedo, Amaro (2010)
The main purpose is the presentation of an outlook of the contemporary role of online social networks and its social impact. The author presents a broad analysis of social networking, communication and social behavior based on a review of updated scientific research.